Characterization of urban mobility behavior in emerging cities of Ethiopia: the case study of Bahir Dar using structural equation modeling - Kassaye, Tafere Yalew; Woldetensae, Berhanu; Ectors, Wim; Uhlmann, Julius; Schneider, Sven; Bielik, Martin; Schmidt, Philippe (Frontiers in Sustainable Cities, 2025)
An in-depth understanding of travel behavior underpins the development of efficient and sustainable urban transport systems. While several studies have examined aspects of urban mobility in Sub-Saharan Africa, comprehensive and in-depth studies remain limited across most cities in the region. Consequently, many urban contexts in this area are still underexplored, particularly in Ethiopia, the mobility dynamics and the factors that influence it are unknown. Therefore, this study explores the urban mobility behavior of emerging cities and its relationships with individual and household attributes in Bahir Dar. To this end, data was collected through a household travel survey from 2,000 participants, selected using cluster and systematic sampling techniques, and analyzed using descriptive statistics, SEM and curve fitting techniques using SPSS, R, and AMOS. The findings showed that the travel characteristics of residents vary among individuals based on personal and household attributes. Overall, Bahir Dar residents made on average 2.4 daily trips, with a trip rate of 2.5 for men predominantly for work and administrative service purposes, and 2.33 trips undertaken by women mainly for shopping, social affairs and health purposes. Demographically, females, the elderly and relatively young group of populations tended to make fewer and shorter distance travels compared to other groups. The results of the structural equation model have proved the relationships between identified characteristics of travelers and their travel behavior. As a result, transport system attributes (β = 0.98), economic characteristics (β = 0.96), household size (β = 0.96), and number of workers in households (β = 0.94) were key factors influencing travel behavior in emerging cities. However, gender, possession of a driving license, and land use variables were found to be less significant in determining the travel behavior of residents. Besides filling the research gap, this study recommends the consideration of travel variations among different socio-demographic and economic groups when developing various city plans, policies and traffic management interventions.